2009
DOI: 10.1186/1478-4505-7-s1-s14
|View full text |Cite
|
Sign up to set email alerts
|

SUPPORT Tools for evidence-informed health Policymaking (STP) 14: Organising and using policy dialogues to support evidence-informed policymaking

Abstract: This article is part of a series written for people responsible for making decisions about health policies and programmes and for those who support these decision makers.Policy dialogues allow research evidence to be considered together with the views, experiences and tacit knowledge of those who will be involved in, or affected by, future decisions about a high-priority issue. Increasing interest in the use of policy dialogues has been fuelled by a number of factors: 1. The recognition of the need for locally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
197
1
19

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(221 citation statements)
references
References 16 publications
4
197
1
19
Order By: Relevance
“…27 Policy dialogue was used in this study because policy dialogues allow research evidence to be considered together with the views, experiences and tacit knowledge of those who will be involved in, or affected by, future decisions about a high priority issue. 10 The policy dialogue allowed for frank, off-therecord deliberations by following the Chatham House Rule 17 and offered a neutral forum to the policymakers and other stakeholders to discuss the policy issues based on comparative evidence and experience. Their frank comments and recommendations on the policy brief enabled the policy brief be more specifically tailored to IDP control in the context of Ebonyi State.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Policy dialogue was used in this study because policy dialogues allow research evidence to be considered together with the views, experiences and tacit knowledge of those who will be involved in, or affected by, future decisions about a high priority issue. 10 The policy dialogue allowed for frank, off-therecord deliberations by following the Chatham House Rule 17 and offered a neutral forum to the policymakers and other stakeholders to discuss the policy issues based on comparative evidence and experience. Their frank comments and recommendations on the policy brief enabled the policy brief be more specifically tailored to IDP control in the context of Ebonyi State.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome was expected because as in the preparation of the policy brief, the policy dialogues were conducted according to well-proven and established guidelines. 17,28,29 The major objective of adopting policy dialogue in this study was to improve the likelihood of taking up research into the policymaking process and this to a great extend was realized.…”
Section: The Quality Of the Design And Process Of The Policy Brief Anmentioning
confidence: 99%
See 2 more Smart Citations
“…EVIPNet teams have been involved in preparing evidence briefs for policy and convening deliberative (policy) dialogues that use those briefs as an input 7,8,9,10 which, taken together, address the majority of the barriers found to hinder the greater use of research evidence (i.e. research isn't highly valued, relevant or easy to use), while building on factors found to increase the likelihood that research will be used to inform policy decisions (e.g.…”
Section: Introductionmentioning
confidence: 99%